2000
DOI: 10.1080/00420980020002850
|View full text |Cite
|
Sign up to set email alerts
|

Street Scenes: Practices of Public and Private Space in Urban Vietnam

Abstract: This paper contributes an initial venture into thinking about the uses of the terms 'public' and `private' space in the context of Vietnamese urban life. It is argued that these terms, while they are critiqued and debated in Western academia, still retain substantial descriptive power at an everyday level. In non-Western societies, however, these terms may be more difficult to apply and the paper provides an empirical section which argues that the boundaries between public and private spaces are fluid and rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
124
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(128 citation statements)
references
References 11 publications
2
124
0
2
Order By: Relevance
“…8 Incidentally, the conical leaf hat is becoming a performance prop all by itself, it would appear from Harms' (2011) findings, whereby street vendors choose to wear traditional garments as part of their improvised "marketing strategy" to sell their homemade goods. 9 For example, Drummond (2000) or Thomas (2001). 10 Interestingly, in 2012 a small-scale gender report in HCMC found that out of 189 respondents, 2% declared to be neither female nor male (LIN Center for Community Development, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…8 Incidentally, the conical leaf hat is becoming a performance prop all by itself, it would appear from Harms' (2011) findings, whereby street vendors choose to wear traditional garments as part of their improvised "marketing strategy" to sell their homemade goods. 9 For example, Drummond (2000) or Thomas (2001). 10 Interestingly, in 2012 a small-scale gender report in HCMC found that out of 189 respondents, 2% declared to be neither female nor male (LIN Center for Community Development, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It is a popular conception that a private space is one free from outside impingements and obligations. However, feminists have pointed out that such a private space may become a site of oppression when one member infringes upon the rights of other members (Drummond 2000(Drummond :2379. Hence, privacy is important, but critical analysis should balance it against competing interests, because protecting one person's privacy might lead to restraints of the freedoms of another (Niessenbaum, 1998:559).…”
Section: What Is a Home?mentioning
confidence: 99%
“…A home may be defined as a domestic space where social patterns are reproduced more or less free from outright control by outside forces such as the State (Drummond 2000(Drummond :2379. It is a popular conception that a private space is one free from outside impingements and obligations.…”
Section: What Is a Home?mentioning
confidence: 99%
“…Despite attempts to internalize daily practices (for example, through indoor plumbing), the lines between outside and inside were less rigid in Quang Trung, and much of life unfolded in its corridors, stairways and communal spaces rather than behind closed doors. This was not only because of cramped living spaces, as Drummond (2000Drummond ( , p 2383) has argued in the case of Hanoi, where housing space per person was much less than in Quang Trung, but also because of culturally and historically specific forms of sociality that emerged in response to infrastructure breakdown. 4 For the older generation who have suffered tremendous hardship and loss during and after decades of war, such sociability -from washing clothes together at the well (despite having water and a washroom in their homes) to sharing a cup of tea at a local kiosk -remains crucial to their quality of life and sense of social well-being.…”
mentioning
confidence: 99%
“…But much ambivalence remained. The towers sold a particular lifestyle that they could not afford (dryers and air conditioners) and that many rejected outright: modern living entailed new spatial relations associated with the privatization and internalization of everyday life in stark contrast to daily practices in social housing and other urban spaces (Drummond, 2000;Yan, 2003;Harms, 2009). Many older residents have remained emotionally connected to Quang Trung on account of its symbolic historical meaning and the intensely social environment ('and village-like relations', according to one resident) that the design inspired (Schwenkel, 2013).…”
mentioning
confidence: 99%